Factors Associated with Maternal Infant Bonding During Early Postpartum Period - Thapa, Madhuri; Mulepati, Sumitra; Lama, Sumana (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Maternal infant bonding is an essential phenomenon that begins in early postpartum period and continues over the next few years. The postpartum is a period where a mother is more likely to develop attachment with her baby. The study aims to determine the relationship between the selected factors and their influence on postpartum mother infant bonding within one to three days after delivery. Methods: A descriptive cross-sectional study was conducted among postpartum women in one to three days after delivery in a tertiary care hospital from January 2023 to April 2023. The responses were collected via convenience sampling and the findings were analyzed using Mann-Whitney U test, Kruskal-Wallis test and ordinal regression. Results: The factors such as occupation (P = 0.02), support of SSC (P = 0.03), and risk of depression (P = 0.00) found to be statistically significant to bonding. The ordinal regression analysis showed that the mother with no risk of depression and involved in business contributed significantly to bonding (χ2 = 6.9, 8.6; Exp. B = 0.3, 0.3; P = 0.00, 0.00 respectively). Conclusions: This study found support of skin to skin contact, no risk of depression and involvement in business to be significant determinants of maternal infant bonding.